Enhancing Elementary Students’ Interest in Science Learning through Worldwall-Based Digital Learning Media - Agustan Syamsuddin; Fahmi Hidayat; Nurlina (Universitas Pendidikan Ganesha, 2025)
This study addresses the persistent problem of low student interest in learning abstract science concepts, particularly changes in the state of matter, which often hinder elementary students’ understanding and engagement. The purpose of this research was to investigate the effect of Worldwall digital learning media on fourth-grade students’ interest in science learning. Using a quasi-experimental design, the study involved fourth-grade students from two elementary schools as research subjects. Data were collected through learning interest questionnaires and classroom observation sheets to capture both self-reported and behavioral engagement. The data were analyzed using descriptive statistics and inferential testing to determine the significance of differences between the experimental and control groups. The findings revealed that the integration of Worldwall significantly increased students’ interest and engagement in learning, as evidenced by higher posttest scores and more active participation during lessons. These results imply that interactive and gamified digital platforms such as Worldwall can serve as effective tools for enhancing motivation and supporting science learning in elementary settings, highlighting the importance of integrating technology-based instructional strategies into classroom practice.